Tropical cities research boundaries: a bibliometric analysis to bridge the gaps through multi-dimensional and cross-disciplinary features - Uchôa, José Gescilam S. M.; Bertotto, Luis E.; dos Santos, Matheus S.; Reis, Alan; Mendiondo, Eduardo M.; Wendland, Edson C. (Frontiers in Sustainable Cities, 2023)
Tropical regions are known for their complex ecosystems and biodiversity, which play a vital role in regulating the global climate. However, researching tropical cities can be challenging due to the need for multi-disciplinary and multi-dimensional approaches. In this study, we conducted a bibliometric analysis to gain a structured understanding of the developments and characteristics of tropical cities research in the last decade. We identified the fundamental influences in tropical cities research, based on four major sub-topics: climate change, sustainable urbanization, protecting biodiversity, and urban resource management. We examined the connections between these themes and performed a systematic literature review on each. Our analysis provides a comprehensive trend analysis of tropical cities, both quantitatively and qualitatively. Our findings aim to provide a solid foundation for bridging the gaps for future crosscutting research.